Motricidade fina na criança: um estudo bibliométrico da literatura nacional e internacional - Coppede, Aline Cirelli (2012)
Fine motor coordination is essential to the intellectual and psychomotor development of a child. The use fine motor skills to manipulate objects and perform functional needs plays a vital role in child development and participation in activities of daily living. Therefore, difficulties in fine motor skills affect school performance and undermine the child s self-esteem and the sense of competence. The objective of this study was to describe how is configured the scientific field of fine motor skills in children national and international databases. In addition, aimed at specifics to analyze the scientific parameters in bibliometric, mapping scientific production within the fine motor components related to body function, participation in activities and environmental factors. The methodology used was bibliometric analysis of the studies recovered on the databases national and international, Banco de teses da CAPES, BVS, ScienceDirect and Scopus. The methodological procedures of the study were divided into the following steps: Step 1 - Review of the literature on Human development, Child Development Motor, Occupational Therapy and Information Science, Step 2 - Data collection and systematization of data; Step 3 - Bibliometric analysis: organization and processing of bibliometric studies collected using the Vantage Point software for bibliometric analysis and MS Excel for graphing and tables for data presentation; Step 4 - Description and analysis of results, recovering the concepts exposed in the theoretical framework on which to base analysis and interpretation of data obtained. At the end of the tudy produced the following bibliometric indicators: the Banco de Teses da Capes the year of greatest production was 2002; the gender of the authors and supervisors who emphasize was the female; the formation of the majority of authors in the field of Physical Education and Physiotherapy; most studies are at Master's level; The University has more studies in the area is UDESC, in the program graduate of Human Movement Science; the funding agency that funds most work is the CAPES; majority of studies are descriptive; the scale is the most used is EDM (Rosa Neto, 2002), the theme more approached is Motor Development; and the studies perspectives have focused functions and structures of the body. Regarding the databases BVS, ScienceDirect and Scopus, the publications have grown over the years, especially 2010; with most records are of collective authorship; the formation of the authors is in Occupational Therapy (33%), Physiotherapy ( 19%) and Physical Education (15%); the predominant language is English; in BVS in the country that indexes articles is Brazil; ScienceDirect and Scopus is in the U.S.; Periodicals that stood out in the BVS was Journal Themes About the Developing; ScienceDirect was Human Movement Science, and the Scopus were Developmental Medicine & Child Neurology (8%), American Journal of OccupationalTherapy (7%) and Physical and Occupational Therapy Pediatrics (5%); and the perspectives of studies have recovered the subject of fine motor anchored in the concepts of structure and functions of the body in three bases (56% - BVS, 69% - ScienceDirect, 71% Scopus); most studies are crosssectional nature (94%) and descriptive (81%); the topics most discussed were: fine motor skills (75%), motor development (35%) children (28%), preschool (27 %) and rating scales (21%); the data collection instruments more used in the articles were tests of fine motor skills not standardized (22%), followed by Scale Peabody (12%), test of motor proficiency of Bruininks-Oseretsky (7%) and M-ABC (7 %); identifies the subject of fine motor related especially with motor development (7%), autism (5%), prematurity (5%) and school context (5%).